EKSISTENSI PABRIK GULA POERWODADIE DAN PENGARUHNYA TERHADAP PERUBAHAN SOSIAL EKONOMI MASYARAKAT DESA PELEM, KECAMATAN KARANGREJO, KABUPATEN MAGETAN - Nurrati, Septi Dini Cumala (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2013)
The purpose of this research is to know: (1) to find out the background of Poerwododadie Sugar Plant in Pelem Village, (2) to find out the development of Poerwododadie Sugar Plant in Pelem Village and (3) to find out the effect of Poerwododadie Sugar Plant on the social economic life of the society in Pelem Village. This study was a descriptive qualitative research, the way of investigating an event in the present by providing descriptive data in the form of written or spoken words from certain people or behavior that can be observed using certain procedures. This research employed a single embedded case study. The data source used was object source, place, event, informant and document; techniques of collecting data used were observation, interview, and document analysis. The sampling technique used was purposive and snowball sampling one. To validate the data, two triangulations techniques, data and method. Technique of analyzing data used was interactive analysis, the one encompassing three components: data reduction, data display, verification/conclusion drawing, proceeding cyclically. Considering the result of research, the following conclusions could be drawn. (1) The background of Purwodadie Sugar Plant establishment derived from Van den Bosch (Dutch Governor General?s idea) applying the compulsive planting system in Indonesia. (2) The development of Purwodadie Sugar Plant experienced fluctuation corresponding to the policy of the occupying government or in domestic condition at that time. (3) The effect of Purwodadie Sugar Plant existence on the society of Pelem Village was very large, in economic sector there was 70% of Pelem Village society working at Purwodadie Sugar Plant either as permanent or temporary workers (labor, foreman, driver, etc), seller and motorcycle driver thereby increasing income and society welfare. Keyword: sugar, industry, social economic, village Pelem